Dependence of glow curve structure on the concentration of dopants in LiF:Mg,Cu,Na,Si thermoluminescent material - Ha, Vu Thi Thai; Hai, Nguyen Thi Quy; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract